Title I, Part A Parent Involvement, 2013-2014. Research Educational Program Report. (Distributed by ERIC Clearinghouse, 2015)
The Title I, Part A program is designed to ensure that all children have a fair, equal, and significant opportunity to obtain a high-quality education and achieve, at a minimum, proficiency on challenging state academic achievement standards and assessments. The program's goal is accomplished by providing supplemental funding for educational programs to Title I, Part A schools, which have a high percentage of students living in poverty. Title I, Part A also includes provisions to engage parents in the education process, which helps schools and parents share accountability for high student achievement. This Title I, Part A Parent Involvement Report for 2013-2014 describes the level of parental involvement in Title I schools, as reported by schools through Chancery, and by families through the Your Voice Survey. Household demographic data are also included, and the data are aggregated by school, school office, and district. Some of the highlights are as follows: (1) Overall, the district had a 72.5 percent parent involvement participation rate recorded in Chancery. Hispanic students (127,288) represented the largest Title I student group districtwide and had a 73.1 percent parent involvement participation rate in Chancery. African American students had the lowest rate at 63.9 percent; (2) The 2013-2014 Your Voice Survey was completed by 23,441 parents of Title I students reflecting 11.9 percent of all Title I students enrolled; (3) According to Chancery, 77.8 percent of parents were identified as having received a copy of the individual/school compact. Among other parent participation categories in Chancery, the category with the highest participation rate was Conference with 42.6 percent and the category with the lowest participation rate was Parent Literacy with 9.6 percent; and (4) The question related to parent involvement from the Your Voice Survey with the highest agreement rate was "My child's school gives opportunities for and encourages me to participate in parent/teacher conferences, school activities, and meetings" with 90.1 percent. The question with the lowest agreement rate was "My child's school gives me the training and materials to help me to help my child" with 75.0 percent.